(3Jbhje GdCHOGf aj JOHjQ GdEfSGbs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s ((3CHh SGde , EHQGgje Hf LGHQ GdeJWHH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb aShi , hbOQ agOi , hCeQVi hCTai s
(3BNQgG (B:s
(3bGd aCi GdChbGJ CdP ? bGd YfO GdfXQ ai UHGMg GfJTGQkG bGd (B: (3ddg OQc ef CYQGHi CYWjJ YdekG , hCJMag hhUdg s
(3Ufag ddebJOi HGddg GdYHGSis
(3hHYV ChQGbgG GdCNjQI eLOOI HNW JYdjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJH GdChd (B- (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs